Comparative study of marital adjustment and life satisfaction among spouses of patients with alcohol dependence and normal healthy control: a case control study - Fatima, Nazish; Panday, Rishi; Rizvi, Abid (International Journal of Research in Medical Sciences, 2017)
Background: Alcohol dependence is associated with domestic violence, which in turn aggravates the physical and emotional distress of the family. Alcohol dependence also leads to decrease in social support not just for the affected individual but for the family. Various studies revealed low level of life satisfaction and among the family members of patients with alcohol dependence. The aim of the study was to compare marital adjustment and life satisfaction among the spouses of patients with alcohol dependence with normal healthy control. Methods: It was cross sectional study conducted at Ranchi Institute of Neuro-Psychiatry and Allied Sciences, Ranchi. Thirty patients with alcohol dependence syndrome with their spouses and 30 age and socio-economic status matched healthy control with their spouses were inducted in the study based on inclusion and exclusion criteria. Spouses of the two groups were compared for their life satisfaction and marital adjustment using life Satisfaction Scale and Marital Adjustment Questioner respectively. Results: There was significant difference in respect to life satisfaction among the spouses of individual with alcohol dependence syndrome and normal healthy control. Life satisfaction as well as marital adjustment was better in spouses of normal healthy control as compared to spouses of patients of alcohol dependence. Conclusions: There is significant difference in respect to life satisfaction among the spouses of individual with alcohol dependence syndrome and normal healthy control. Wives of normal healthy control had better marital adjustment as compared to spouses of alcohol dependence syndrome. There was positive co-relation between life satisfaction and marital adjustment.